2012
DOI: 10.1039/c2cp40527j
|View full text |Cite
|
Sign up to set email alerts
|

Metals on graphene: correlation between adatom adsorption behavior and growth morphology

Abstract: We present a systematic study of metal adatom adsorption on graphene by ab initio calculations. The calculations cover alkali metals, sp-simple metals, 3d and group 10 transition metals, noble metals, as well as rare earth metals. The correlation between the adatom adsorption properties and the growth morphology of the metals on graphene is also investigated. We show that the growth morphology is related to the ratio of the metal adsorption energy to its bulk cohesive energy (E(a)/E(c)) and the diffusion barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
183
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(206 citation statements)
references
References 42 publications
20
183
3
Order By: Relevance
“…The adsorption energy of a Pt (Ru) adatom on freestanding MLG has the value ∼ −1.6 eV (−2.0 eV) and the diffusion barrier has the value ∼0.17 eV (0.62 eV). 26,31 Thus, the interaction of Pt with graphene is somewhat weaker than that of Ru. There also exist DFT results for the adsorption energy (E ads ) in preferred fcc region for these metals on supported MLG/Ru(0001): ∼ −2.8 eV for Pt versus −2.6 eV for Ru.…”
Section: Background: Theory Modeling For Nc Formation On Mlg/rumentioning
confidence: 99%
“…The adsorption energy of a Pt (Ru) adatom on freestanding MLG has the value ∼ −1.6 eV (−2.0 eV) and the diffusion barrier has the value ∼0.17 eV (0.62 eV). 26,31 Thus, the interaction of Pt with graphene is somewhat weaker than that of Ru. There also exist DFT results for the adsorption energy (E ads ) in preferred fcc region for these metals on supported MLG/Ru(0001): ∼ −2.8 eV for Pt versus −2.6 eV for Ru.…”
Section: Background: Theory Modeling For Nc Formation On Mlg/rumentioning
confidence: 99%
“…Note that transition metals preferentially adsorb on hcp regions [27], indicating a different adsorption mechanism than for rare earths. Calculations show that rare earths on freestanding graphene present similarities with alkali metals, with a bond that is mainly ionic and the charge transferred from the atom to the graphene delocalized over several graphene cells [31]. For Cs on gr/Ir(111), density functional theory (DFT) calculations found that adsorption is favored in the vicinity of the atop region of the moiré cell [25].…”
Section: Adsorption Site In the Moiré Cellmentioning
confidence: 99%
“…Only for higher temperatures, dimers form by lateral attachment of adatoms diffusing toward each other from far distances. This is indicative of a repulsion between the atoms that can only be overcome for T > 50 K. This repulsion is very likely electrostatic, since rare-earth atoms, similar to alkali atoms [24,31], are expected to transfer electrons to graphene [25,31,32], resulting in positively charged adatoms.…”
Section: A Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the nature of an exposed 2D electron system open to environment, many studies have been carried out in examining how adsorption of metal adatoms on graphene sheet can modify its electronic transport properties for electronics, sensors and energy applications [3][4][5][6]. Indeed, in tin decorated graphene sheets a tunable superconducting phase transition was observed [7].…”
mentioning
confidence: 99%